Solvent‐Free Aerosol Deposition for Highly Luminescent and Thermally Stable Perovskite‐Ceramic Nanocomposite Film. Issue 13 (12th May 2019) - Kim, Sunghoon; Cho, Myung‐Yeon; Kim, Ik‐Soo; Kim, Won‐Jung; Park, Sung‐Han; Baek, Seungmin; Oh, Jong‐Min; Kim, Sang‐Wook
Abstract: Luminescent perovskite structure has been used in a polymer‐encapsulated form for display applications. However, insulating polymers as a host matrix are intrinsically vulnerable to thermal stresses which cause softening distortion or deterioration in thermoplastic polymers. Here, nanostructured CsPbBr3 /Al2 O3 composite film is developed by aerosol deposition method. At first, CsPbBr3 /Al2 O3 composite powders with bright and saturated green emission are synthesized. Then, the ceramic composite powder comprising monoclinic CsPbBr3 nanocrystals supported on submicron α‐Al2 O3 particles is successfully transformed to a film‐type by aerosol deposition, which enables a nonsolvent‐induced process at room temperature. The deposited films show a pure green spectrum with a narrow full width at half maximum of 17 nm, high long‐term stability at 150 °C for over 20 d, and an absolute photoluminescence quantum yield of 8%–15%. In general, inorganic films are known to have difficulty with flexibility and patterns. However, the deposited film can be employed in useful applications such as down‐converting materials for an LCD backlight with a wide‐color gamut of 89.2% in Rec. 2020, highly flexible ceramic composite films, multilayer films, patterning of surfaces for an advanced color filter array, and deposition on curved substrates toward diverse display fields. Abstract : CsPbBr3 nanocrystals supported on α‐Al2 O3 particles are synthesized and transformed to the film type via aerosol deposition. This film has extraordinary long‐term stability at high temperature and emits pure green color (522 nm and full width at half maximum of 17 nm). The film has useful applications such as DC materials for an LCD backlight, flexible films, surfaces patterning, and deposition on curved substrates.